Dementia and Clinical Interaction in Frontline Radiography: Mapping the Practical Experiences of Junior Clinicians in the UK. (April 2019) - Miller, Paul K; Booth, Lisa; Spacey, Adam
This paper reports findings from a study of the practical experiences of junior diagnostic radiographers in the UK when managing patients with dementia. Extended semi-structured interviews with six participants (mean experience in diagnostic radiography = 3.5 years) were analysed using interpretative phenomenological analysis. Findings highlight that participants' recurrently cited lack of confidence around their knowledge of dementia, and regular treatment of the condition as a 'generic' thing in practice, had sometimes damaged clinical interaction, particularly when the participant was feeling institutional time pressures. Education for new professionals was seen as lacking in both quantity and context-relevance, with implications for professional confidence and ethical practice. Carers and family members were viewed by participants as potentially positive and negative forces within an examination context, and technological advances in radiography were taken to be clinically advantageous but also actively detrimental to the effective interpersonal care of their patients.